Determinants of High Blood Pressure Management among Patients with a Complication of Stroke : A Case of Meru Teaching and Referral Hospital (MeTRH) - KATHAMBI, PURITY; Kailemia, Peter (Meru Universty of Science and Technology International Conference (MUSTIC), 2025)
Background: Non-communicable diseases (NCDs) are the current leading cause of global morbidity and mortality contributing an estimated 71% (41 million) of the all-cause mortality in 2016 (WHO, 2018). Factors like high blood pressure, smoking, diabetes, high cholesterol, obesity and atrial fibrillation causes stroke. Stroke deaths accounted for 6% of total deaths in Kenya in 2020. Main Objective: To explore determinants influencing the management of high blood pressure among patients diagnosed with stroke preceding a period of treatment for hypertension visiting MeTRH. Methodology: Mixed method research approach will be used where explanatory sequential study will be carried out. Quantitative study will use simple random sampling and qualitative study purposive sampling. The study population are patients with stroke seeking care at Meru Teaching and Referral Hospital, healthcare workers in NCD clinic and medical records for stroke patients. A sample size of 72 medical records, 7 healthcare workers and data saturation for patients will be used. To collect Quantitative data, semi structured interviews and structured surveys from healthcare workers and for medical records using pre-designed semi structured questionnaire. To collect Qualitative data, individual open ended surveys questions and unstructured interviews to patients with stroke will be used. Quantitative data will be entered into Statistical Package for Social Sciences (SPSS) version 24 and descriptive statistics used for analysis then presented using frequency tables and graphs. Reading and re-reading data will be done qualitative design and presented as a report. Test and retest reliability method and cronbach’s Alpha of 0.8 will be used to ascertain reliability and WHO Stroke Steps questionnaire for validity. Ethical clearance will be sought from Meru University of Science and Technology (MUST) Institutional Research Ethics Review Committee (MIRERC) and obtain permit from National Commission of Science and Technology and Innovation (NACOSTI). Informed consent will be sought from the study participants.